A new start for the Journal of Integrated Information Management (JIIM) - Giannakopoulos , Georgios (Journal of Integrated Information Management, 2024)
It is with pleasure to welcome you again to a new start of our former publishing endeavour. The Journal of Integrated Information Management (JIIM), after three years of silence is making a dynamic comeback in academic publishing, under the auspices of the Department of Archival, Library and Information Studies, coinciding with the founding of the University of West Attica and the nesting of the Department in it. JIIM is a multidisciplinary, blind peer-reviewed journal that publishes original research on all aspects and issues regarding Information Science and Integrated Information Management. Based on the common ground of cultural organisations (Libraries Archives Museums) informational functions, JIIM expands its interest to scientific, administrative and business aspects of Information Science & Management, as well as to related social sciences and the humanities. JIIM provides immediate open access to its content abiding to the principle that making research freely available to the public supports a greater global exchange of knowledge. Thus, I am taking this opportunity to express my gratitude to the Advisory Board and the Editorial team for their contribution, their trust and eagerness to participate. We are aiming at making JIIM a reputable scientific communication channel and we are now welcoming submissions for the upcoming journal issues.